Kawasaki Disease Presenting Uncommonly with Torticollis: A Case Report - Hassan Mottaghi Moghaddam Shahri; Faeze Keihanian; Mohammad Hassan Nezafati; Mohammad Saeid Sasan (Clinical Case Reports)
ABSTRACT Kawasaki disease (KD) is an acute, febrile, systemic inflammatory disorder affecting children. A subset of KD patients, often infants or older children, does not meet the classic diagnostic criteria. In such cases, delayed recognition of atypical or incomplete KD can increase the risk of coronary artery complications. We report the case of a previously healthy 7‐year‐old girl who initially presented with isolated cervical adenitis, without fever, conjunctivitis, or extremity edema. She was initially treated for an infectious disease. After 10 days, additional clinical features emerged, raising suspicion for atypical KD. Subsequent evaluation revealed giant coronary artery aneurysms, necessitating coronary artery bypass graft surgery (CABG), aneurysmectomy, and aneurysmorrhaphy to prevent complications such as aneurysm rupture. She remained asymptomatic during a two‐year follow‐up period. This case highlights the importance of maintaining a high index of suspicion for KD in children presenting with lymphadenopathy and unusual clinical features, especially when empirical antibiotic therapy is ineffective. Early recognition and treatment are crucial to prevent serious cardiac complications.